Essentials of Thyroid Cancer Management - Mazzaferri, Ernest L.; Amdur, Robert J.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Much has changed in the diagnosis and treatment of thyroid cancer over the past five years. Essentials of Thyroid Cancer Management provides clinicians from all disciplines with the information they need to manage patients correctly. Each chapter focuses on a specific clinical situation with the major points explained using tables and figures. A teaching atlas is included for neck ultrasonography and the interpretation of whole body radioiodine scans. Examples of topics that are covered include: *Evaluation of a thyroid nodule *Total versus hemi thyroidectomy *Neck dissection for positive nodes *Thyroid remnant ablation with I-131 *Preparation for remnant ablation with recombinant human TSH *Follow-up with recombinant human TSH-stimulated Tg measurements *Testing for tumor persistence *Treatment of persistent disease *External beam radiotherapy *Management of distant metastases using recombinant human TSH *Using molecular markers of medullary carcinoma Series editor comments: "Benign and malignant tumors of the thyroid are relatively common lesions. The management of thyroid cancer is multi-disciplinary involving Endocrinologists, Surgeons, Nuclear Medicine Physicians, and Medical and Radiation Oncologists. This text provides a comprehensive review of current management issues by leading investigators in the field." Steven T. Rosen, M.D. Series Editor.
Basic Thyroid Anatomy -- Thyroid and Parathyroid Physiology -- Pathology and Classification Of Thyroid Carcinoma -- The American Joint Committee on Cancer System of Staging Thyroid Cancer -- The Diagnosis of Thyroid Cancer -- Definitions: Thyroid Uptake Measurement, Thyroid Scan, and Whole Body Scan -- Thyroid Stunning -- The Role of a Diagnostic Radioiodine Whole Body Scan (DxWBS) -- The Value of a Post-Treatment Whole Body Scan -- Examples of Radioiodine Whole Body Scans -- Computerized Tomography (CT) and Magnetic Resonance (MR) Imaging of Thyroid Cancer -- Positron Emission Tomography (PET) of Thyroid Cancer -- Neck Ultrasonography in Patients with Thyroid Cancer -- Incidence, Prevalence, Recurrence, and Mortality of Differentiated Thyroid Cancer -- Factors that Predict Cancer Recurrence and Death from Differentiated Thyroid Cancer -- A Total Thyroidectomy Rarely Removes All Thyroid Tissue -- Neck Dissections to Remove Malignant Lymph Nodes -- Potential Complications of Thyroid Cancer Surgery -- Half-Life and Emission Products of I-131 -- Choosing the Activity of I-131 for Therapy -- Requirements for Outpatient Release Following I-131 Therapy -- A Checklist of Things to do at the Clinic Visit Prior to I-131 Therapy -- A Checklist of Things to do on the Day of I-131 Administration -- Documents that Facilitate I-131 Scheduling and Patient Education -- The Low-Iodine Diet -- Intravenous Iodinated Contrast Effects Iodine Uptake for Months -- Measuring Urinary Iodine (UI) -- Using Lithium Carbonate to Increase the Effectiveness of I-131 -- Thyroid Hormone Withdrawal to Elevate TSH -- Recombinant Human TSH: Background Information and Standard Protocol -- Using rhTSH Prior to I-131 Therapy -- I-131 Therapy in a Patient with a Small Thyroid Remnant -- I-131 Therapy in a Patient with a Large Thyroid Remnant -- Effects of Suppressing Thyrotropin on Tumor Growth and Recurrence -- Potential Side Effects and Complications of I-131 Therapy -- Management of Xerostomia, Taste Impairment and Dental Prophlaxis -- An Overview of Follow-Up of Differentiated Thyroid Cancer -- Follow-Up of Differentiated Thyroid Cancer Using Serum Thyroglobulin Measurements -- Overview of Management of Differentiated Thyroid Carcinoma in Patients with Negative Whole Body Radioiodine Scans and Elevated Serum Thyroglobulin Levels -- Treatment Guidelines When the Only Evidence of Disease is an Elevated Serum Thyroglobulin Level -- Treatment of Residual Differentiated Thyroid Cancer in the Neck and Mediastinum -- Treatment of Lung Metastases from Differentiated Thyroid Cancer -- Treatment of Bone Metastases from Differentiated Thyroid Cancer -- Treatment of Spinal Cord Compression from Metastatic Thyroid Cancer -- Treatment of Brain Metastasis from Differentiated Thyroid Cancer -- Management of Differentiated Thyroid Cancer During Pregnancy -- Thyroid Cancer Originating in a Thyroglossal Duct Remnant -- Tall and Collumnar Variants of Papillary Carcinoma -- Diffuse Sclerosing Variant of Papillary Carcinoma -- Hürthle Cell Carcinoma -- Insular and other Poorly Differentiated Thyroid Carcinomas -- Anaplastic Carcinoma -- Diagnosis and Management of Medullary Thyroid Carcinoma -- External Beam Radiotherapy Dose Schedules -- Indications for External Beam Radiation Therapy for Differentiated Thyroid Cancer -- Sequencing of I-131 and External Beam Radiation Therapy for Differentiated Thyroid Cancer -- Indications for EBRT for Medullary and Anaplastic Thyroid Carcinoma -- Conventional Radiotherapy Technique for Treating Thyroid Cancer -- Intensity Modulated Radiation Therapy for Thyroid Cancer -- Drawing Target Volumes for Intensity Modulated Radiation Therapy for Thyroid Cancer -- Potential Toxicity of External Beam Radiotherapy for Thyroid Cancer -- Resource Websites.
Keywords: Oncology .; Radiotherapy; Endocrinology .; Radiology; Nuclear medicine; Oncology; Radiotherapy; Endocrinology; Imaging / Radiology; Nuclear Medicine